The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1111/j.1523-1739.2006.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Harvesting of Source Populations for Translocation: a Case Study with New Zealand Robins

Abstract: Reintroductions are conducted frequently throughout the world, and some source populations are harvested repeatedly to provide animals for translocation. The responses of these source populations to harvest should be monitored, and the resulting data used to refine population models will guide management. After North Island Robins ( Petroica longipes) were reintroduced to Tiritiri Matangi, New Zealand, in 1992, the population became a source for robins for additional reintroductions in the region. We construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 39 publications
0
71
0
Order By: Relevance
“…Even if it was 50% of this estimate (85), removing 12 juvenile fodies a season is unlikely to have had a significant negative impact on the population dynamics of this subpopulation. Dimond and Armstrong [2007] found that a population of North Island robins Petroica longipes with a reproduction rate of 2.32 fledglings per female per year could maintain a carrying capacity of 65 birds with an annual harvest of 12 juveniles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if it was 50% of this estimate (85), removing 12 juvenile fodies a season is unlikely to have had a significant negative impact on the population dynamics of this subpopulation. Dimond and Armstrong [2007] found that a population of North Island robins Petroica longipes with a reproduction rate of 2.32 fledglings per female per year could maintain a carrying capacity of 65 birds with an annual harvest of 12 juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these programs have focused on birds of prey [Seddon et al, 2005] and the in-situ rearing of endangered passerines seems to have been restricted to North America [Kuehler et al, 1995[Kuehler et al, , 2000. Translocation of adult passerines onto islands has been successfully used in the Seychelles [Komdeur, 1994] and New Zealand Dimond and Armstrong, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…(Dimond & Armstrong 2007). Previous studies on New Zealand parakeets have focused on remnant populations on the New Zealand mainland (Elliot et al 1996) and on a few offshore islands with alien mammalian predators (Greene 2003) that are known to adversely affect nesting birds (O'Donnell 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These issues include the rescaling of red list indices, the investigation of other red list criteria than abundance (such as trends or range area), the consideration of genetic processes and the extension of the analysis to the meta-population scale. At an even wider spatial scale, species-based assessments should balance the benefit of local reintroduced populations with the impact to the source population (Dimond & Armstrong, 2007) and other remnant populations (Le Gouar et al, 2008;Mihoub et al, 2011), and here again, the IUCN status, assessed at the regional or global level, provides a promising framework. More generally, whatever the spatial scale considered, we need to go beyond demography and address the wider ecological impacts of translocations (especially those not conducted in the species range), the perception of success by people (Ewen et al, 2014) and the global, macroevolutionary biodiversity benefits of restoring species and populations.…”
mentioning
confidence: 99%